Economic evaluation of Zea mays silage and fodder as alternative nutrition of cattle in high plains (Revista Sistemas de Producción Agroecológicos, 2015)
The work was done on a cattle farm in the village of La Guardiana of the municipality of San Martin de los Llanos in scenic class III floors high plains, in order to determine the most viable economic option in the production of silage for feeding cattle on plots where the following treatments were established: Zea mays and cutting grass Pennisetum purpureum in monoculture and associated with the legume Mucuna deeringiana (Bort) Merr). The study area is 350 meters above sea level, temperature and average precipitation of 24°C and 3.200 mm, there treatments with an experimental design were established in randomized block into 4 plots each with four replicates for a total of 16 plots, with an area of 5.000 m2, with the entire experiment than 80.000 m2. 20 samples of fresh forage in 1 m2 of each plot are manually taken; which were weighed to calculate performance and ensiled fresh forage and silage per hectare. The plots were grown, harvested and ensiled calculating the cost per hectare, with this information and the commercial cost economic analysis. The biomass yield in fresh fodder, showed the best results in the treatment that involved Zea mays with Mucuna deeringiana (Bort) Merr being of 66.110 kg/ha, followed by Zea mays with 65.406 kg/ha, being the lowest Pennisetum purpureum in monoculture with 30.434 kg/ha. The variable biomass yield in silage showed the highest yield in association with Mucuna deeringiana (Bort) Merr with Zea mays (61.181 kg/ha), followed by Zea mays with (60.649 kg/ha) and Pennisetum purpureum 30.000 kg/ha. It was shown in the economic analysis that most performance was achieved ensiling Zea mays in partnership with Mucuna deeringiana (Bort) Merr, generating COP$6.931.807  per hectare of ensiled biomass, followed by Zea mays in monoculture with COP$6.871.532 being the lowest Pennisetum purpureum in monoculture COP$3.399.000.
Keywords: forage crops; Pennisetum purpureum; corn; Mucuna deeringiana